2019
DOI: 10.1007/s00128-019-02678-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Microplastic Types and Surfactant-Microplastic Mixtures Under Fasting and Feeding Conditions: A Case Study on Daphnia magna

Abstract: This study evaluates the mortality and immobilization on Daphnia magna after 24-96 h of exposure to microplastic disper-sions (PP, PE, PVC, PVC/PE), and to microplastic + surfactant solutions both under fasting and feeding conditions. The tested microplastics were analysed with μFT-IR to determine their chemical composition, purity, and dimensions. The results show that: (i) exposure under fasting conditions produces acceptable results on negative controls no later than 24 h; (ii) the disper-sion of microplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 28 publications
(42 reference statements)
3
19
0
Order By: Relevance
“…Dispersions were made by suspension of tested particles in UNI EN ISO 6341:2012 standard freshwater. Experiments previously reported [28,29] determine for each toxicant the dose permitting the survival of a significant fraction of the tested population until the end of the exposure time (96 h).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersions were made by suspension of tested particles in UNI EN ISO 6341:2012 standard freshwater. Experiments previously reported [28,29] determine for each toxicant the dose permitting the survival of a significant fraction of the tested population until the end of the exposure time (96 h).…”
Section: Experimental Designmentioning
confidence: 99%
“…ZnO and n-TiO 2 were tested at 1.12 and 113.18 mg/L respectively; microplastic doses were 0.05 mg/L. The selection of microplastics to be tested was done according to Renzi et al [29].…”
Section: Experimental Designmentioning
confidence: 99%
“…Surfactants are also added during the synthesis of MP which could alter the surface characteristics and thus the adsorption process [8,9]. Nevertheless, surfactants can also bias experiments: Renzi et al [10] recorded a higher mortality and immobilization in toxicological experiments with MP when the surfactant Triton X-100 was used. The surfactant itself had negative effects on the organisms but the more stable dispersion of particles could also lead to increased ingestion and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research focuses only on few polymer types, most often on polystyrene (PS) and polyethylene (PE) particles, disregarding other polymer types of high production and consumption, such as polypropylene (PP) and polyvinyl chloride (PVC;PlasticsEurope, 2015;S a et al, 2018). However, the toxicity of microplastics may also depend on the polymer type or on the chemicals that a plastic product, and therefore its fragments, contain (Renzi et al, 2019). One single plastic product can contain hundreds of chemicals .…”
Section: Tables and Figures Tablementioning
confidence: 99%
“…Irregular PLA microplastics (3.4 mm; 19.6 mg/L) did not affect feeding, size and population growth of D. magna upon chronic exposure (Gerdes, 2018). In a comparative analysis of irregular PVC, PP and PE particles (10e100 mm; 50 mg/L), PP and PE induced a higher acute toxicity than PVC on D. magna under fasting conditions (Renzi et al, 2019). Schrank et al (2019) compared irregular rigid and flexible PVC (4e276 mm) and reported delay of primiparity in D. magna upon exposure to rigid PVC and alterations in body lengths and reproductive output for flexible PVC.…”
Section: Microplastic Effects On Daphnia Magna Depend On the Plastic Typementioning
confidence: 99%